Determining the safety and efficacy of dietary supplementation with 3ˊ-sialyllactose or 6ˊ-sialyllactose on growth, tolerance, and brain sialic acid concentrations - Golden, Rebecca K.; Sutkus, Loretta T.; Bauer, Laura L.; Donovan, Sharon M.; Dilger, Ryan N. (Frontiers in Nutrition, 2023)
Sialylated oligosaccharides, including 3ˊ-sialyllactose (3ˊ-SL) and 6ˊ-sialyllactose (6ˊ-SL), comprise a large portion of human milk and have been known to support development over the first year of life. While research has investigated the impact of early-life supplementation, longer-term supplementation remains relatively unexplored. Consequently, the following study assesses the impact of supplementation of either 3ˊ-SL or 6ˊ-SL on growth performance, tolerance, and brain sialic acid concentrations. Two-day-old piglets (n = 75) were randomly assigned to a commercial milk replacer ad libitum without or with 3ˊ-SL or 6ˊ-SL (added at 0.2673% on an as-is basis). Daily body weight and feed disappearance were recorded to assess growth performance and tolerance. Pigs were euthanized for sample collection on postnatal day 33 (n=30) or 61 (n=33), respectively. Across growth performance, clinical chemistry and hematology, histomorphology, and sialic acid quantification, dietary differences were largely unremarkable at either time-point. Overall, SA was well-tolerated both short-term and long-term.